Reliability of the Penetration Aspiration Scale With Flexible Endoscopic Evaluation of Swallowing. (June 2015) - Butler, Susan G.; Markley, Lisa; Sanders, Brian; Stuart, Andrew
Objectives: The Penetration Aspiration Scale (PAS), although designed for videofluoroscopy, has been utilized with flexible endoscopic evaluation of swallowing (FEES) in both research and clinical practice. The purpose of this investigation was to determine inter- and intrarater reliability of the PAS with FEES as a function of clinician FEES experience and retest interval. Methods: Three groups of 3 clinicians (N = 9) with varying FEES experience (beginning, intermediate, and advanced) assigned PAS scores to 35 swallows. Initial ratings were repeated following short-term (ie, 1 day) and long-term (ie, 1 week) retest intervals. Results: Intraclass correlation coefficients were calculated to assess interrater reliability on the first rating for each group. The coefficients were .91, .82, and .89 for the beginning, intermediate, and advanced clinicians, respectively. Overall interrater reliability across all 9 clinicians, irrespective of experience, was .85. Intraclass correlation coefficients were also calculated to assess intrarater reliability. The intrarater reliability for short- and long-term ratings was .90, .94, and .96 and .96, .97, and .94 for the beginning, intermediate, and advanced clinicians, respectively. Overall intrarater reliability across all 9 clinicians and all 3 ratings was .94. Conclusions: Excellent inter- and intrarater reliability was evidenced with the application of the PAS for FEES regardless of clinician experience and retest interval.